Assessment of Exams at Atenea, an IMS LTI Application for Scalability Problems - Marc Alier; María José Casany; Ariadna Llorens; Jesús Alcober; Joana d’Arc Prat (New Visions in Science and Technology Vol. 11, 2021)
The online teaching support platform was changed by the Universitat Politècnica de Catalunya in 2004. Moodle, an open source software, was used in place of the prior proprietary software. The population’s confinement at home owing to the COVID-19 pandemic in 2020 was a stress test for the whole university community, particularly those responsible for providing support for the online teaching support platform. Concerns about possible scalability challenges with the quiz functionality during the examination period arose as a result of the increased activity and the prospect of the generalization of online assessment. The solution included deploying a high-performance version of the Moodle Quiz Module As A Service (SaaS) to plug-and-play within the university’s LMS without relying on internal resources using Moodle’s IMS LTI interoperability features. This study aims at analyzing the solution, which included a systems strategy, private cloud operations, internal communication, and teacher training, that allowed the university course to be assessed in a confined space.